Dual method use among long-acting reversible contraceptive users. (4th March 2018) - Bernard, Caitlin; Zhao, Qiuhong; Peipert, Jeffrey F.
Abstract: Objective: To compare rates of dual method use (concurrent use of condoms and an effective method of contraception) in long-acting reversible contraceptive (LARC) and non-LARC hormonal contraceptive users, and to determine factors associated with dual method use. Methods: We conducted a secondary analysis of the Contraceptive CHOICE Project, an observational, prospective cohort study of 9256 women in St. Louis, MO, USA. Our sample included 6744 women who initiated a contraceptive method within 3 months of enrollment, continued use at 6 months post-enrollment, and responded regarding dual method use. Our primary outcome was the rate of dual method use at 6 months post-enrollment. Results: Dual method use was reported by 32% of LARC and 45% of non-LARC hormonal contraceptive users ( p  < .01). After adjusting for other covariates and comparing to non-LARC hormonal contraceptive users, LARC users were less likely to report dual method use (RRadj 0.76, 95% CI 0.70–0.83). Factors associated with dual method use in our multivariable analysis were age <25 years, black race, lower education, single relationship status, baseline dual method use, baseline diagnosis of sexually transmitted infection (STI), greater partner willingness to use a condom, and higher condom self-efficacy score. Conclusions: LARC users are less likely to report dual method use compared to non-LARC hormonal contraceptive users, but other factors also impact dual method use. Further studies should be performed to determine whether this lower dual method use increases the risk of STI. Clinical trials registration: Clinicaltrials.gov Identifier NCT01986439.